The Exploring of Deep Learning Lived Experiences in 5-6 Years Old Children in Constructive Play Activities: A Phenomenological Study in Kindergarten - Ardhana Reswari; Danang Prastyo; Selfi Lailiyatul Iftitah (Universitas Pendidikan Ganesha, 2025)
Early childhood education should focus not only on learning outcomes but also on meaningful and deep learning processes. However, implementing deep learning in ECE remains challenging due to limited understanding of how children experience learning, particularly in constructive play activities. This study aims to explore the lived experiences of deep learning among children aged 5–6 years during constructive play activities. The study employed a qualitative approach with a descriptive phenomenological design. The research participants consisted of 12 children aged 5–6 years and 5 kindergarten teachers. Data were collected through semi-structured interviews, observations during constructive play activities, and visual documentation. Data were analyzed using Colaizzi’s phenomenological analysis procedures to identify the essence of children's learning experiences. The findings reveal four dimensions of deep learning experiences: sensory and physical engagement, emotional and value integration, cognitive and metacognitive strategies, and social interaction with symbolic perspectives. Children perceive constructive play as a space for exploration, idea development, and the transformation of materials into meaningful symbols. Deep learning emerges through an experiential cycle that includes openness to experience, active engagement in problem-solving, progressively deeper understanding, and the integration of knowledge. These findings extend the conceptualization of deep learning as a holistic learning experience and provide practical implications for early childhood educators in designing meaningful, reflective, and enjoyable learning environments.